PENGARUH KUALITAS KEHIDUPAN KERJA,LOYALITAS KARYAWAN, DAN WORK LIFE BALANCE TERHADAP KINERJA KARYAWAN PT ARTAJASA PEMBAYARAN ELEKTRONIS - Siti Rachmawati Mailani, (2022)
This study is a quantitative study with the aim of testing and knowing the infulence of Quality of Work Life, Employee Loyalty, and Work Life Balance on Employee Performance of PT Artajasa Electronic Payments. This study uses a sample size of 100 respondents who are employees of the IT and Operations Directorate of PT Artajasa Electronic Payments. The analytical technique used in this research is the Coefficient of Determination Test, T Test (Partial) and F Test (Simultaneous) using Smart PLS 3.0 software. The test results show that (1) Quality of work life has a significant effect on employee performance at PT Artajasa electronic payments, (2) Employee loyalty has a significant effect on employee performance at PT Artajasa Electronic Payments, (3) Work life balance has no significant effect on employee performance at PT Artajasa Electronic Payments, and (4) Quality of Work Life, Employee Loyalty, and Work Life Balance have a significant effect jointly on the Employee Performance of PT Artajasa Electronic Payments.